The Effect of Various Bur Types and Two Bonding Agents on Shear Bond Strength of Composite Resin to Dentin - Wiaam M AL-Ashou (University of Mosul, College of Dentistry, 2012)
The aims of this in vitro study was to assess the effectiveness of various bur types and bonding agents on the shear bond strength of composite resin to dentin. Eighty non carious, extracted human molars were mounted in acrylic resin, the occlusal surface of all the teeth were grounded to obtain flat dentin surface. After that the teeth were randomly divided into four groups (n=20) according to the bur types that will be used to prepare the dentin surface. After preparation of dentin each group was divided into two subgroups (n=10) according to the type of adhesive systems used (Excite & I-Bond), the adhesive systems were applied to the dentin surface and light-cured according to manufacturers instructions. A 4mm high composite cylinder was incrementally built up. After that, specimens stored for one month at 37ºc in distilled water and thermo cycled for 500 cycles between (5ºc & 55ºc) and then tested in a universal testing machine. The results of this study demonstrated that the method of surface prepa-ration affected the shear bond strength of I-Bond and this is not true for Exit system, when the dentin surface prepared with fissure burs the shear bond strength greater than when the surface prepared with round burs. The results of this study also showed that the groups in which Excite bonding agent used have greater value of shear bond than the groups treated with I-Bond.